Balance Training Enhances Vestibular Function and Reduces Overactive Proprioceptive Feedback in Elderly - Wiesmeier, Isabella K.; Dalin, Daniela; Wehrle, Anja; Granacher, Urs; Muehlbauer, Thomas; Dietterle, Joerg; Weiller, Cornelius; Gollhofer, Albert; Maurer, Christoph (Frontiers in Aging Neuroscience, 2017)
Objectives Postural control in elderly people is impaired by degradations of sensory, motor, and higher-level adaptive mechanisms. Here, we characterize the effects of a progressive balance training program on these postural control impairments using a brain network model based on system identification techniques. Methods and Material We analyzed postural control of 35 healthy elderly subjects and compared findings to data from 35 healthy young volunteers. Eighteen elderly subjects performed a 10 week balance training conducted twice per week. Balance training was carried out in static and dynamic movement states, on support surfaces with different elastic compliances, under different visual conditions and motor tasks. Postural control was characterized by spontaneous sway and postural reactions to pseudorandom anterior-posterior tilts of the support surface. Data were interpreted using a parameter identification procedure based on a brain network model. Results With balance training, the elderly subjects significantly reduced their overly large postural reactions and approximated those of younger subjects. Less significant differences between elderly and young subjects’ postural control, namely larger spontaneous sway amplitudes, velocities, and frequencies, larger overall time delays and a weaker motor feedback compared to young subjects were not significantly affected by the balance training. Conclusion Balance training reduced overactive proprioceptive feedback and restored vestibular orientation in elderly. Based on the assumption of a linear deterioration of postural control across the life span, the training effect can be extrapolated as a juvenescence of 10 years. This study points to a considerable benefit of a continuous balance training in elderly, even without any sensorimotor deficits.